Authentic Assessment - Mujahidin, Mujahidin (EDUCATIO : Journal of Education, 2016)
In the era of Competency-Based Curriculum / School-Based Curriculum, the assessment emphasizes students performance in each subject. They are required to acquire not only the cognitive aspect but Also the performance aspect. One assessment models relevant to this is the authentic assessment. Such an assessment emphasizes students ability to meaningfully demonstrate the knowledge they have acquired. The assessment not only Asks questions about the knowledge they have acquired, but requires the actual performance Also relevant to the knowledge. There are some differences between a traditional assessment and an authentic assessment. The former emphasizes the elicitation of knowledge the students have acquired through objective tests, while the latter emphasizes the tasks that the make the students practice learning outcomes meaningfully in real life, reflecting the mastery of knowledge and skills in a particular subject. The Necessary steps to develop an authentic assessment include (1) setting the standard; (2) assigning authentic tasks; (3) selecting the criteria; and (4) designing the rubric. One popular authentic assessment at present is the portfolio assessment models. This models is a class-based assessment conducted during the learning process. A portfolio is a collection of students works systematically arranged during A Certain learning period, used to monitor the development of the students knowledge, skills, and attitudes in a particular subject.